An Overview on Underutilized Wild Edible Plants as a Source of Alternative Nutrition (International Journal of Innovative Research in Computer Science & Technology, 2021)
Ensuring a stable, hygienic, as well as  nutritious food supplies for the poor and undernourished  people of emerging economies is a serious concern today.  Scarcity, high cost, and intermittent supply of healthy  food have led to the hunt for an inexpensive or alternative  source of excellent and nutritious food in relatively  underdeveloped countries. Underutilized edible wild  plants like Canavalia, Mucuna, Rhynchosia, Afzelia,  Brachystegia, and Detarium, for instance, have been  examined as well as proved to have high nutritional  content. The number of plant species are healthy, and  some have medicinal properties, as per existing studies.  The usage of underutilized wild edible plants helps to  combat hunger also improves rural health of the public.  This study also looked at how underused wild edible  plants may be exploited commercially as a source of  nutritional supplements, novel food compositions, bio  fortification, and product design.
Keywords: Alternative; Nutritional Value; Potential Source; Underutilized; Wild Edible Plants